How does a CBT-based transdiagnostic program for separation anxiety symptoms work in children? Effects of Super Skills for Life - Mireia Orgilés; Elena Garrigós; José Pedro Espada; Alexandra Morales (Revista de Psicología Clínica con Niños y Adolescentes, 2020)
Super Skills for Life (SSL) is a transdiagnostic program of Anglo-Saxon origin based on cognitive behavioural therapy, aimed at treating emotional problems in children. It has been translated and implemented in the Spanish population, achieving significant reductions in anxious and depressive symptoms. The objective of the current study was to examine the short- and long-term efficacy of SSL in schoolchildren with separation anxiety. The program was attended by 86 Spanish-speaking children aged 8-12 years, who were evaluated before receiving the intervention, immediately after and 12 months later. Results indicated statistically significant improvements both in the main problem, separation anxiety and other comorbid symptoms or problems (depression, behaviour problems, problems with peers, interference of anxiety in daily life, etc.). Overall, the results show that the program was more effective in the long-term than in the short-term. The findings of the study suggest that SSL can be useful for treating emotional problems in children with separation anxiety. Clinical implications of these findings are discussed.